Kajian Teoritis Integrasi Teknologi dan Bioekonomi dalam Meningkatkan Produktivitas Pertanian - Rian Aditya; Muhsinun Muhsinun (Journal of Science and Technology: Alpha, 2025)
The integration of technology and bioeconomy presents a promising theoretical framework for enhancing agricultural productivity in response to global challenges such as climate change, food insecurity, and resource depletion. This study offers a conceptual analysis of how technological innovations—including precision agriculture, digital monitoring systems, and biotechnology—can be synergized with bioeconomic principles to optimize input efficiency, reduce environmental impact, and promote sustainable agricultural practices. Drawing from interdisciplinary literature, the paper explores key theoretical models such as sustainable intensification, circular bioeconomy, and smart farming systems, emphasizing their potential to transform traditional agricultural paradigms. Furthermore, the study examines the economic implications of this integration, highlighting its role in improving farm-level profitability, strengthening rural economies, and supporting policy development for sustainable agriculture. By synthesizing scientific and economic perspectives, this theoretical inquiry contributes to a deeper understanding of how innovation-driven, bio-based strategies can reshape agricultural systems toward greater resilience and sustainability. The findings underscore the importance of continued research and policy alignment to operationalize these concepts in diverse agroecological and socioeconomic contexts.